2004
DOI: 10.1055/s-2004-818952
|View full text |Cite
|
Sign up to set email alerts
|

Polysaccharides fromHibiscus sabdariffaFlowers Stimulate Proliferation and Differentiation of Human Keratinocytes

Abstract: Raw polysaccharides, previously described in detail, were isolated from the flowers of Hibiscus sabdariffa L. and fractionated by ion exchange chromatography into one neutral and three acidic subfractions. Raw polysaccharides and all acidic subfractions caused a strong induction of proliferation of human keratinocytes (HaCaT) of up to 40 %, while the neutral polymers were ineffective. While mitochondrial activity was not influenced, raw polysaccharides induced early differentiation of primary natural human ker… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(7 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…Since arabinan and arabinogalactan chains covalently linked to RG-I structures have been associated with strong biological activities [3] and especially keratinocyte proliferation and differentiation [6,9,10,11], we wanted to investigate the structural characteristics of three extracts - an arabinan and two AG-II type RG-I polysaccharides - with the aim to characterize the variability of their properties and then to identify the structural origin of their bioactivity. Mr 27,000 heat shock protein (HSP-27) is a member of the small heat shock protein family.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Since arabinan and arabinogalactan chains covalently linked to RG-I structures have been associated with strong biological activities [3] and especially keratinocyte proliferation and differentiation [6,9,10,11], we wanted to investigate the structural characteristics of three extracts - an arabinan and two AG-II type RG-I polysaccharides - with the aim to characterize the variability of their properties and then to identify the structural origin of their bioactivity. Mr 27,000 heat shock protein (HSP-27) is a member of the small heat shock protein family.…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, increased degrees of polymerization as well as extensive branching and ramification seem to enhance their biological activities [8]. Rhamnogalacturonan from Hibiscus sabdariffa was shown to stimulate the proliferation and differentiation of human keratinocytes [9]. Deters and coworkers recently suggested that terminal arabinose residues of type I RG arabinogalactan side chains [10], as well as rhamnose content [11], could justify the observed bio-activity of pectins.…”
Section: Introductionmentioning
confidence: 99%
“…The Roselle plant ( Hibiscus sabdariffa ) is a shrub with the characteristic five petals, funnel shaped flower belonging to the malvaceae family ( Brunold et al . 2004 ).…”
Section: Introductionmentioning
confidence: 99%
“…18 In a separate study, arabinose, galactose, glucose, rhamnose, galacturonic acid, glucuronic acid, mannose, and xylose were identified in calyces by ion-exchange chromatography. 19 Twelve phenolic compounds, glucose, and fructose, along with other nutrients, were identified by one study on flowers of H. sabdarif fa, and a second study reported 18 phenolic compounds from flowers. 20,21 Hibiscus seeds contain mainly volatile compounds such as unsaturated hydrocarbons, alcohols, and aldehydes.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Recently, ultraperformance liquid chromatography coupled to electrospray ionization quadrupole-time-of-flight mass spectrometry (UPLC-ESI-Q-TOF-MS n ) was used to identify 33 phytochemicals, which included hydroxycinnamic acids, organic acids, anthocyanins, and flavonoids from H. sabdariffa calyces . In a separate study, arabinose, galactose, glucose, rhamnose, galacturonic acid, glucuronic acid, mannose, and xylose were identified in calyces by ion-exchange chromatography . Twelve phenolic compounds, glucose, and fructose, along with other nutrients, were identified by one study on flowers of H. sabdariffa , and a second study reported 18 phenolic compounds from flowers. , Hibiscus seeds contain mainly volatile compounds such as unsaturated hydrocarbons, alcohols, and aldehydes .…”
Section: Introductionmentioning
confidence: 99%